Deep Inguinal Ring Medial to the Inferior Epigastric Vessels: A Novel Finding - Domingos, Pedro Henrique; Rojas, Maria Clara Trevisan; Zanusso, Júlia Presotto; Rissi, Renato (Brazilian Journal of Case Reports, 2026)
The deep inguinal ring is a critical anatomical landmark in groin hernia repair and is classically described as an opening in the transversalis fascia located lateral to the inferior epigastric vessels. Variations in its position have been reported; however, a relationship in which the ring lies medial to the inferior epigastric vessels has not previously been described. We report a rare anatomical finding observed during routine cadaveric dissection of a male specimen. The specimen was sectioned transversely at the level of the iliac crest and sagittally through the pubic symphysis and linea alba, preserving the lower left anterior abdominal wall. Upon dissection of the inguinal region, the deep inguinal ring was identified medial to the inferior epigastric vessels and within the boundaries of Hesselbach’s triangle. The spermatic cord structures traversed this opening and followed the expected course through the inguinal canal. Macroscopic examination demonstrated preserved continuity of the surrounding transversalis fascia, and no hernia sac or herniated tissue was identified. Because no clinical or demographic information was available, the origin of this configuration could not be determined and a previously acquired pathological process cannot be completely excluded. Recognition of such an anatomical variation may be important during radiological evaluation and open, laparoscopic, or robotic groin surgery, where the inferior epigastric vessels are routinely used as landmarks for hernia classification and operative planning. To our knowledge, this finding has not been previously documented in the literature.